2015
DOI: 10.5152/tpa.2015.2281
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and laboratory findings in the differential diagnosis of central precocious puberty and premature thelarche

Abstract: Aim: In this study, it was aimed to evaluate the clinical, antropometric and laboratory findings of female patients diagnosed with central precocious puberty and to determine the laboratory value with the best diagnostic accuracy in the diagnosis of central precocious puberty. Material and Methods: Female patients whose breast development began before the age of 8 years were included in the study. The data of the patients were obtained by retrospectively examining file records. The chronogical age, age at the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
16
0
4

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 22 publications
2
16
0
4
Order By: Relevance
“…Several studies have focused on investigating a single gonadotropin biomarker to identify patients with CPP conveniently. Basal or peak serum luteinizing hormone (LH), follicle-stimulation hormone (FSH), and the ratio LH/FSH are the most common biomarkers reported [3-7]. However, the cut-off values of these single biomarkers depend on the assay used to measure the gonadotropin levels.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have focused on investigating a single gonadotropin biomarker to identify patients with CPP conveniently. Basal or peak serum luteinizing hormone (LH), follicle-stimulation hormone (FSH), and the ratio LH/FSH are the most common biomarkers reported [3-7]. However, the cut-off values of these single biomarkers depend on the assay used to measure the gonadotropin levels.…”
Section: Introductionmentioning
confidence: 99%
“…Puberty is the period when pulsatile release of the gonadotropin releasing hormone (GnRH) starts as a result of activation of Hypothalamic-Pituitary-Gonadal (HPG) axis and the secondary sex characteristics develop. Central precocious puberty (CPP) is defined as development of secondary sex characteristics in relation to activation of the HPG axis before the age of 8 years in girls and before the age of 9 years in boys [ 1 ]. GnRH analogues (GnRHa) represent the treatment of choice in central precocious puberty, because arresting pubertal development and reducing either growth velocity or bone maturation should improve adult height [ 2 ].…”
Section: Introductionmentioning
confidence: 99%
“…In previous studies, the threshold values for basal FSH were found to range between 1.9 and 2.25 IU/L ( 15 , 28 ). However, it has been reported that basal FSH values were not sufficiently reliable and discriminative in the differentiation of CPP and PT, because these threshold values had low sensitivity and specificity.…”
Section: Discussionmentioning
confidence: 95%